2017
DOI: 10.1002/ijgo.12122
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective cohort study of hospital versus home care for pregnant women with preterm prelabor rupture of membranes

Abstract: Maternal and newborn outcomes were similar between women who received PCAH and those who were managed in hospital. The reduced resource use in PCAH might lead to cost savings without compromising outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
17
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 11 publications
9
17
0
6
Order By: Relevance
“…In fact, most of the papers analyzed reported higher rates: 23.9% (18), 34.7% (9), 35% (46), 47% (8), 53% (47), and 67.1% (7). However, there were also studies with comparatively lower rates: 20.2% (49); 17.4% (21); 16.5% (37), 14.6% (10); 12% (19); 9% (20); and 2.4% (11). However, in the latter case (11), only 29.7% of the sample had PPROM, and the great majority were >37 weeks of gestation.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, most of the papers analyzed reported higher rates: 23.9% (18), 34.7% (9), 35% (46), 47% (8), 53% (47), and 67.1% (7). However, there were also studies with comparatively lower rates: 20.2% (49); 17.4% (21); 16.5% (37), 14.6% (10); 12% (19); 9% (20); and 2.4% (11). However, in the latter case (11), only 29.7% of the sample had PPROM, and the great majority were >37 weeks of gestation.…”
Section: Discussionmentioning
confidence: 99%
“…Three retrospective studies have shown that maternal outcomes (chorioamnionitis, mode of delivery) and neonatal outcomes (hospitalization in intensive care units, respiratory distress syndrome, intraventricular hemorrhage) were comparable between outpatients and inpatients, but these studies suffer from selection bias 14,27–29 . Indeed, most of the women in outpatient care were different from inpatients because of specific eligibility criteria with better prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, comparative studies found no significant differences in the rate of major complications, including chorioamnionitis, between the study groups 33 , 34 , 37 , 38 , 40 , 41 .…”
Section: Discussionmentioning
confidence: 80%
“…The clear benefit of outpatient management compared to inpatient care is the significantly shorter hospital stay 30 , 34 , 38 , 40 , 50 , which in combination with a significantly shorter length of stay of preterm infants on the neonatal intensive care unit results in considerable savings in treatment (hospital) costs 29 , 30 , 51 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation